2002
DOI: 10.1021/ja028030k
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Activity of a Novel Cyclic Seleninate Ester as a Glutathione Peroxidase Mimetic and Its Facile in Situ Generation from Allyl 3-Hydroxypropyl Selenide

Abstract: 1,2-Oxaselenolane Se-oxide is a novel cyclic seleninate ester that functions as a remarkably efficient glutathione peroxidase mimetic by catalyzing the reduction of tert-butyl hydroperoxide to tert-butyl alcohol in the presence of benzyl thiol. The seleninate ester can be conveniently generated in situ by oxidation of allyl 3-hydroxypropyl selenide with tert-butyl hydroperoxide. Its catalytic activity surpasses that of several other known GPx mimetics containing cyclic selenenamide structures, which were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
89
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(89 citation statements)
references
References 19 publications
0
89
0
Order By: Relevance
“…[3][4][5][6] However, its use under nonenzymic conditions as a catalyst for hydrogen peroxide oxidation of thiols to disulfides gave poor results. Recently, Back et al 7,8 have demonstrated the exceptional glutathione peroxidase-like activity of the simple bis(3-hydroxypropyl) selenide and the unexpected role of its oxidation product, spirodioxaselenanone, as an intermediate in the catalytic redox cycle for GPx.In view of the known role of organoselenium compounds in biological systems, [9][10][11][12] in addition to their unique characteristics in organic synthesis, 13 the design and synthesis of novel organoselenium compounds with potential biological activity constitutes an ongoing challenge. Recently, we have found that in situ prepared selenium dichloride, readily obtained from elemental selenium and sulfuryl chloride, 14 undergoes smooth 1,2-addition to the triple bond of various propargylic alcohols resulting in the formation of symmetrical (Z,Z)-bis(1-hydroxymethyl-2-chlorovinyl) selenides 1 in high yields and in completely regio-and stereospecific manner (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] However, its use under nonenzymic conditions as a catalyst for hydrogen peroxide oxidation of thiols to disulfides gave poor results. Recently, Back et al 7,8 have demonstrated the exceptional glutathione peroxidase-like activity of the simple bis(3-hydroxypropyl) selenide and the unexpected role of its oxidation product, spirodioxaselenanone, as an intermediate in the catalytic redox cycle for GPx.In view of the known role of organoselenium compounds in biological systems, [9][10][11][12] in addition to their unique characteristics in organic synthesis, 13 the design and synthesis of novel organoselenium compounds with potential biological activity constitutes an ongoing challenge. Recently, we have found that in situ prepared selenium dichloride, readily obtained from elemental selenium and sulfuryl chloride, 14 undergoes smooth 1,2-addition to the triple bond of various propargylic alcohols resulting in the formation of symmetrical (Z,Z)-bis(1-hydroxymethyl-2-chlorovinyl) selenides 1 in high yields and in completely regio-and stereospecific manner (Scheme 1).…”
mentioning
confidence: 99%
“…[3][4][5][6] However, its use under nonenzymic conditions as a catalyst for hydrogen peroxide oxidation of thiols to disulfides gave poor results. Recently, Back et al 7,8 have demonstrated the exceptional glutathione peroxidase-like activity of the simple bis (3-hydroxypropyl) selenide and the unexpected role of its oxidation product, spirodioxaselenanone, as an intermediate in the catalytic redox cycle for GPx.…”
mentioning
confidence: 99%
“…They observed that 22 actually was a pro-catalyst that generates the unusual cyclic seleninate ester 23 through a series of oxidation reactions and sigmatropic rearrangement steps upon the GPx like reaction conditions. 23 The novel heterocycle 23 was significantly more effective as a GPx mimic than ebselen 6. Furthermore, the same group also described the synthesis of selenide 24.…”
Section: Organoselenium Compoundsmentioning
confidence: 96%
“…Hence, the design, synthesis, and evaluation of small-molecule selenium compounds that mimic the biological activity of GPx have been investigated by several groups, and selected examples 2 [28], 3 [29], 4 [30], and 5 [31] are presented in Scheme 2. Various diaryl diselenides [32][33][34][35][36][37][38] and certain types of tellurium compounds as well as dendrimeric and cyclodextrin-derived organochalcogen catalysts that emulate GPx have also been reported [39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%